What Characterizes Education in Women's Universities in Japan? An Analysis of Diploma Policies - Chie Sugino (MDPI AG, 2023)
Women's universities were established in post-war Japan to fill the gender gap in higher education. Although they attract fewer students today than in the past, they account for nearly 10% of all universities nationwide. This study focuses on the diploma policies (DPs) that all universities in Japan are required to publish and explores the characteristics of education at women's universities by comparing the DPs of 22 women's and 59 co-educational universities. The DP content was analyzed using a cross-tabulation search engine employing text-mining. The results indicate that the DPs of women's universities highlight their priority to foster economically sustained women, which reflects their founding purpose of empowering women. Although both women's and co-educational universities emphasize their relationship with society, the latter seem to view society as something their graduates can create and develop, while the former regards it as given or changing. Moreover, women's universities appear to emphasize that their graduates play an active but not a leading role in society. This could be an indication of gender inequality in the social, economic, and political realms of Japan. Considering Japanese society is becoming globalized and diverse, future research should focus on how global values and competencies manifest themselves in DPs.